NAVIGATING THE COMPLEXITIES OF LAND ACQUISITION IN GURUGRAM: ISSUES AND CHALLENGES - Dr. Preeti Raj, (IJRDO - Journal of Social Science and Humanities Research, 2025)
Land is always considered a symbol of an individual's social status. Its acquisition in Gurugram, a prominent city in the state of Haryana, Ind presents a multifaceted landscape characterized by rapid urbanization, regulatory frameworks, socio-economic dynamics, and environmental considerations. This article delves into the intricate nuances of land acquisition in Gurugram, exploring the challenges faced by various stakeholders, proposing potential solutions, and outlining future prospects for sustainable development.